Estrategias agroecológicas urbanas para mitigar la disrupción de los sistemas agroalimentarios convencionales en el barrio Nueva Esperanza, Cantón Ambato, Provincia de Tungurahua en el periodo 2019-2020. - Padilla Carrillo, Jazmina Monserrath (2020)
The current health emergency that our country is going through due to covid-19 has forced the authorities of our country to decree social isolation. This situation has generated an economic and food crisis. The food crisis that generated the pandemic has resulted in the food security of a social and family nucleus being compromised since the availability and access to abundant, safe, nutritious and healthy food is limited. This measure has tended to work with the community of the Nueva Esperanza neighborhood, to generate new agroecological strategies. The purpose of this research was to identify the limitations in the provision of fresh food (vegetables) in the neighborhood environment in order to establish urban agroecological strategies for food production, with the production of micro vegetables that is carried out in the sector determine the acceptability of vegetables produced in the home environment. Through this strategy, the potential of the inhabitants against ecological strategies is explored. Each of the homes was given its own benefits because large spaces are not required for their production. As results obtained, it was possible to establish the urban agro ecological strategy in each household to ensure the provision of food as it is a feasible, easy to carry out, and beneficial way for health and the environment, thus generating an assurance of micro-vegetables to families and savings economic. And it was determined that the main causes for the supply of food is the closure of markets, and the lack of transportation.